2010
DOI: 10.1111/j.2040-1124.2010.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of resistin polymorphism, its serum levels and prevalence of stroke in Japanese type 2 diabetic patients

Abstract: Aims/Introduction:  Resistin, an inflammatory cytokine, might be involved in the development of atherosclerosis. In a recent paper, we showed that resistin polymorphism might be a risk marker for stroke susceptibility in Japanese type 2 diabetic patients. We tested whether the serum resistin levels might be also a risk marker of stroke independently from RETN polymorphism.Materials and Methods:  Type 2 diabetic outpatients from our hospitals were enrolled. Patients (n = 89) with a history of coronary heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Investigating Japanese residents over age 40, Osawa discovered not only a positive correlation between the serum resistin level and the occurrence of angiocardiopathy, but an increase in the rate of ischemic accidents induced by an increasing resistin level as well [ 18 ]. The results of Tsukahara and Osawa were also supported by other research, such as the finding of a higher risk for CI in patients with high resistin level and the GG gene type carriers of site rs1862513 announced by Nakashima [ 19 ]. Targeting CI patients, the resistin level influenced not only their disability rates but also their mortality [ 20 ].…”
supporting
confidence: 62%
“…Investigating Japanese residents over age 40, Osawa discovered not only a positive correlation between the serum resistin level and the occurrence of angiocardiopathy, but an increase in the rate of ischemic accidents induced by an increasing resistin level as well [ 18 ]. The results of Tsukahara and Osawa were also supported by other research, such as the finding of a higher risk for CI in patients with high resistin level and the GG gene type carriers of site rs1862513 announced by Nakashima [ 19 ]. Targeting CI patients, the resistin level influenced not only their disability rates but also their mortality [ 20 ].…”
supporting
confidence: 62%
“…At the same time, they also had increased levels of triglycerides and higher prevalence of MetS and obesity [ 61 ]. In both females and males, the G allele of the 420C/G of the resistin gene polymorphism appears to be associated [ 70 ] with higher risk for cardiovascular events [ 61 ], cerebrovascular disease, and stroke [ 69 , 71 ]: more severe stroke and higher in-hospital mortality in patients with acute ischemic stroke [ 72 ]. Similarly, subjects with allele 299A (allele +299 (G>A) alleles) exhibited high glucose levels at birth, and in diabetic patients, the resistin levels correlated with cerebrovascular disease especially in males [ 72 ].…”
Section: Adipokines As Biomarkers In Atherosclerotic Heart Diseasementioning
confidence: 99%
“…We and others reported that serum resistin levels are increased in a genotype‐dependent manner based on the RETN polymorphism at –420 (C > G). We also showed that the genotyping of this polymorphism might be a good risk marker for stroke susceptibility in Japanese type 2 diabetic patients in a recent paper. However, there have been some conflicting reports that do not support a relationship between the blood resistin levels and susceptibility to cardiovascular diseases.…”
mentioning
confidence: 70%
“…We showed in a previous paper that resistin polymorphism and serum resistin levels might be a risk marker for stroke susceptibility in Japanese type 2 diabetic patients. Resistin levels in blood might be regulated by genetic factors in Asians, but also resistin itself might affect the progression of atherosclerotic diseases. We and others reported that serum resistin levels are increased in a genotype‐dependent manner based on the RETN polymorphism at –420 (C > G).…”
mentioning
confidence: 93%